Strengthening School Resilience in Facing Potential Psycho-Social Hazards in Children - Widowati, Evi; Wahyuningsih, Anik Setyo; Hendriyani, Rulita; Putri, Risa Anggita; Febriananda, Hanif Satria; Anisa, Aza Putri; Wahid, Ayu Fadilah; Laksana, Pungky Indrawan Dwi (Universitas Negeri Semarang, 2024)
Psycho-social hazards in children at school include violence against children, peer victimization, discrimination, heavy academic pressure and bullying. The impact of psycho-social hazards on children is very serious, such as children becoming low self-esteem, aggressive, depressed, injured, drug abuse, experiencing personality disorders, tending to want to hurt themselves and even wanting to commit suicide. On the other hand, parenting styles, students' socio-economic conditions and the influence of gadgets and social media can make children more exposed to psycho-social hazards, whether at school, in their families or in the environment where they live. Manifestations of existing problems include students committing physical violence at school, mocking friends, and even threatening their school friends, whether the school knows about it or not. The aim of this activity is to increase children's knowledge regarding potential psycho-social hazards at school and know how to prevent them. Implementation methods include: 1) preparation stage, 2) implementation stage and 3) evaluation stage. This activity has received an ethical certificate no. 313/KEPK/FK/KLE/2024 from the Health Research Ethics Commission, Faculty of Medicine, UNNES. The results of this activity obtained an increase in teacher knowledge by 2 points, namely from an average of 83 to 85, while the average student knowledge increased significantly, namely from 53 to 80 (an increase of 27 points). Therefore, learning innovation through various media, including educational game media, is very necessary to accelerate the increase in children's knowledge which can be obtained more enjoyably.